Metastases and the Normalization of Tumour Blood Vessels by ICRF 159: A New Type of Drug Action. Issue 5800 (4th March 1972) - Le Serve, A. W.; Hellmann, K.
Abstract : Profound modification of the structure and arrangement of the blood vessels has been shown in tumours after treatment with ICRF 159. X -ray angiography, carbon black (Pelikan ink) labelling, and intravital staining with lissamine green were used to demonstrate the changes. Alteration of the morphology of the blood vessels at the edge of a tumour may affect the escape of malignant cells and the rate of blood flow (and thus the concentration of anticancer drugs) through the tumour.